Política monetária de racionamento de crédito e juros altos no Brasil em 2000-2009: modelo macroeconométrico neo-keynesiano - CARVALHO, David Ferreira (Associação Keynesiana Brasileira, 2022)
The present article sought to evaluate the performance of the monetary policy of credit rationing in Brazil, especially the behavior of the offer of private bank credits in view of the variations in the default rate of corporate borrowers and, also, of the basic interest rate determined by Central Bank, in the post-implementation period of the macroeconomic tripod until the months that followed the onset of the subprime crisis. In view of the presented scenario, the fundamental objective of this article is to formalize an empirical application based on the theory of credit rationing by Joseph Eugene Stiglitz and by neo-Keynesian authors, applied to the case of the Brazilian money market, in view of the high interest monetary policy in the period between June 2000 and March 2009. The main conclusion is that, despite the rigidity of interest rates on loans, the rationing of bank credit in Brazil is due, on the one hand, to the policy high interest rate and, on the other hand, for the cautious behavior of banks for fear of default, marked by excessive prudence and, above all, by the high basic interest rate.